Does Customer Loyalty Depend on Corporate Social Responsibility? - Stanisavljević Milena (Naše gospodarstvo/Our economy, 2017)
This paper presents the results of a study conducted to examine the dependence of customer loyalty on corporate social responsibility (CSR). CSR is a good opportunity for a company’s differentiation, but only if customers value the company’s efforts in this field. Loyalty is a primary goal of each company, but it is influenced by numerous factors. The goal of this paper was to examine if CSR influences customer loyalty as one possible factor. Based on the presented results, management recommendations are provided concerning business strategy, mission, and vision formulation, so companies can fulfill customers’ interests and gain their loyalty.